The influence of the TGT learning model on cooperation attitudes and student learning outcomes in volleyball materials - Ashwani, Zakia Azi; Widiyatmoko, Fajar Ari; Pradipta, Galih Dwi (Jurnal Ilmu Keolahragaan, 2025)
Background. Physical education learning requires effective learning models to improve student learning outcomes and cooperative attitudes. The Teams Games Tournament (TGT) model is a potential alternative to be applied in volleyball learning. Objectives. This study aims to determine the influence of the TGT learning model on learning outcomes and cooperative attitudes of students in volleyball materials. Methods. This study used a quasi-experimental design with Randomized Pretest-Posttest Control Group Design. The research population was all grade VII students of Junior High School Institut Indonesia Semarang, with class VIID as the experimental class and class VIIB as the control class. The sampling technique used Random Sampling. Data collection techniques included observation, written tests, and cooperative attitude questionnaires. Data analysis used t-test with the help of SPSS 27 for windows application. Results. The results showed a significant difference between pretest and posttest scores in the experimental class with a significance value of 0.001 (